Menguak Motif Dibalik Initial Public Offering Studi pada PT Lovina Beach Brewery Tbk - Gunawan, Putu Wahyu; Darmawan, Nyoman Ari Surya (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
This research examines the business journey of PT Lovina Beach Brewery Tbk, an alcoholic beverage industry company operating in Bali, as well as the reasons and motives of the company in carrying out its Initial Public Offering (IPO). The research method used is qualitative with a descriptive approach. Data were collected through in-depth interviews, document analysis, and observations of the dynamics at the business location and the company's environment. Data analysis was performed using triangulation techniques to ensure the validity and reliability of the findings. The main focus of the research is the socio-cultural aspects of Bali, which are very influential in the IPO process and the company's motivation for conducting the IPO. This research found that social, cultural, and religious aspects have significant implications for the company's business journey from its inception to the IPO. This research found three main motives in the implementation of PT Lovina Beach Brewery Tbk's IPO, namely: (1) funding motives for expansion and increased production capacity, (2) motives for increasing company prestige related to strengthening image and branding through stock listing on the stock exchange, and (3) synergy motives with sister companies within the group through cross-ownership. This research contributes to the development of IPO motive theory and provides considerations for business actors in the mikol industry in IPO strategies with local wisdom, as well as for the government or capital market authorities in formulating policies related to the strictly regulated mikol industry.